THE COLLOCATION OF ENGLISH TEXTBOOK FOR GRADE X IN SENIOR HIGH SCHOOL - Sylvia Ulitha Prisscilia Hutapea; Masitowarni Siregar; Nora Ronita Dewi (Universitas Negeri Medan, 2018)
The aims of this study are to find out the types of collocation used in the English textbook for grade X students in senior high school, to find out the most dominant used of collocation, and to describe how the collocations applied in the 3 genre texts contained in the textbook. The data of this study were the collocations used in 3 genre texts, descriptive, recount, and narrative of an English textbook for tenth grade students in senior high school. After analysing the data, the researcher found 6 types of collocations used in the 3 genre text. The result showed that the textbook use 6 types of collocations (adjective + noun, verb + noun, noun + noun, verb + preposition, verb + adverb, adverb + adjective), and the most dominant collocation used was the adjective + noun type of collocation. The use of collocation in the narrative text was the biggest percentage of (38%), followed by the recount text of (35%) and the last was the descriptive text of (27%).Keywords: Collocation, Types of collocations, Genre Text, English Textbook.